Photoconductive Schottky diode based on Al/p-Si/SnS2/Ag for optical sensor applications - Gupta, R. K.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2012)
The Schottky barrier junctions of tin disulfide (SnS2) on p-silicon were fabricated using sol-gel spin technique. The photoresponse and junction properties of the diode were investigated. The ideality factor and barrier height of the Al/p-Si/SnS2/Ag diode were obtained to be 1.54 and 0.53 eV, respectively. The photocurrent properties of the device under various illuminations were also explored. The photocurrent in the reverse bias voltage is increased by increasing photo-illumination intensity. The transient photocurrent results indicate that photocurrent under illumination is higher that the dark current. The capacitance-voltage characteristics of diode were also investigated at different frequencies. The capacitance decreases with increasing frequency due to a continuous distribution of the interface states. These results suggest that the fabricated diode can be used for optical sensor applications. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Tin disulfide; Photoresponse; Schottky diode; Sol-gel; Current-voltage; Capacitance-voltage